Model Dakwah Fardiyah Tarekat Qodiriyah wa Naqsabandiyah - Dadan Suherdiana (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2009)
Da’wah can be done with  model medley,  one of it named  ad-da’wah fardiyah that was done by tarekat Qadiriyah wa naqsabandiyah's fellow men. Unique characteristic of model it lays in mention or greeting in the context relationship between them; mursyid's call to teachers, sheikh for tarekat's founder, murid for what do bailing knowledge, ikhwan for each member. Naming or use of greeting word purpose is not pointless even have particular implication to attitude, interaction and teaching pattern between them.